2020
DOI: 10.3389/fpubh.2020.589331
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Training Need for Epidemic Control in Three Metropolitans: Implications for COVID-19 Preparedness in Vietnam

Abstract: Upon the outbreak of the COVID-19 pandemic, countries worldwide face a critical shortage of human resources in the health sector. Medical students are a potential task force with the capability to support the stretched health sector. This study aims to evaluate their training need for epidemic control in order to employ them effectively. A cross-sectional study was conducted using a web-based survey from December 2019 to February 2020. There were 5,786 observations collected using the snowball sampling techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Therefore, expanding the application of hand sanitizing by strategically placing hand sanitizers in high-traffic public places (e.g., malls, restaurants, and libraries), promoting the dissemination of up-to-date information on regulations and policies for COVID-19 prevention through the mass media [ 35 ], providing training programs for medical students that includes both theoretical and contextual approaches [ 36 ], and targeted communication to the public to improve compliance with hygiene behaviours could be worth the government’s attention [ 37 ]. Public health workers must increase public identification of preventive behaviours to foster daily exercise and hand-washing habits in the wake of the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, expanding the application of hand sanitizing by strategically placing hand sanitizers in high-traffic public places (e.g., malls, restaurants, and libraries), promoting the dissemination of up-to-date information on regulations and policies for COVID-19 prevention through the mass media [ 35 ], providing training programs for medical students that includes both theoretical and contextual approaches [ 36 ], and targeted communication to the public to improve compliance with hygiene behaviours could be worth the government’s attention [ 37 ]. Public health workers must increase public identification of preventive behaviours to foster daily exercise and hand-washing habits in the wake of the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Though the WHO and several other national and international agencies are trying to educate the people worldwide to fight against the pandemic by providing knowledge on several health topics related to COVID-19, they have not succeeded in ending the pandemic so far. 24 , 25 COVID-19 has been a challenge for everyone, including HCWs and medical laboratory personnel. MLS are among the frontline workers who deal directly with the infectious specimen putting their own health at risk to control the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the main information sources for disease prevention that these groups usually consult will encourage the adoption of more effective communication strategies with regard to these topics, so that people can acquire enough accurate knowledge to minimize the propagation of misleading information among the local public (Tran et al, 2020c ). Some studies have shown that medical students can play a more effective role in controlling an outbreak if they receive training in pandemic control and if any gaps in their training needs are addressed (Nguyen et al, 2020 ). For regions with high-risk characteristics in public health emergencies, training and playing the leading role of relevant subjects can reduce the public’s psychological insecurity and anxiety.…”
Section: Conclusion and Discussionmentioning
confidence: 99%